Social Network Analysis of Indonesia Migrant Workers in Hong Kong: Study Social Integration Between Health Care and “KOTKIHO” - Dyah Kuntorini Dwi Angreni (LPPM Universitas Malikussaleh, 2022)
In the research, the relationship between the social networks of migrant domestic workers from Indonesia in Hong Kong and the accessibility of medical care and legal protection is investigated. To help others and support the struggle of BMI organizations and groups in Hong Kong, the Coalition of Indonesian Labor Organizations in Hong Kong (KOTKIHO) was founded out of concern and solidarity.. Similarly, participant observations from formal and informal activities were used in this research, which also drew on field notes. In order to control risk and gain access to resources for their health and well-being, KOTKIHO strategically use their strong and weak ties, deciding within their social network who and what to discuss with reference to medical issues. For characterizing and assessing the continuous dynamic social integration process, researchers suggest using social network analysis. Their employers, who can also provide them with access to institutional and social resources, are carefully negotiated with regarding their rights and opportunities. Participate in online discussions and debates regarding the health policies of their native and host nations. To better comprehend the complexity and intricacy of social integration, social network analysis must be done using a mixed-methods approach due to its limitations as a relatively new tool in the field of social integration research. It also demonstrates the establishment, activation, and mobilization of migrant social networks around discourses on state-designed immigration-related health policy